Case study on kinematics study of single leg landing of national netball player - Ang, Shi Qi (2010)
In Singapore and many other countries worldwide, anterior cruciate ligament (ACL) rupture is common among elite netball players. The main objective of this study is to investigate how kinematics of the lower extremities changes with varying landing height (20cm, 30cm and 40cm). One subject from the National Netball Open Team participated in this exploratory study. Three dimensional kinematics and ground reaction forces are recorded using Qualisys® for single leg landing. Moments and joint reaction force are calculated using inverse dynamic equations using Visual 3D®. Comparisons between the dominant and non-dominant leg are also done. These ACL indicators such as knee abduction, peak VGRF, lateral GRF and knee extensor moment increase with landing height. Henceforth, increment in landing height will put the subject in a higher risk of having ACL injuries. The dominant leg uses more range of motion by bending hip and knee more which increases damping. Therefore, a lower VGRF, internal joint force is observed in the dominant leg compared to the non-dominant leg. However, a greater dynamic valgus moment that includes hip adduction, knee abduction angle and internal hip rotation is observed in the dominant leg. Hence, the dominant leg is at a higher risk of ACL injuries.